2006
DOI: 10.1245/aso.2006.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Management of Well-Differentiated Thyroglossal Remnant Thyroid Carcinoma: Time To Close the Debate? Report of Five New Cases and Proposal of a Definitive Algorithm for Treatment

Abstract: TGDR carcinoma is a rare malignant tumor that is usually diagnosed after surgery; papillary carcinoma is the most common type. The currently recommended treatment is a Sistrunk procedure, with a tendency to deferred total thyroidectomy in selected cases (similar criteria exist for papillary carcinoma of the thyroid gland). The prognosis is excellent, with a good long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
167
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(175 citation statements)
references
References 28 publications
2
167
0
6
Order By: Relevance
“…The reported incidence of carcinoma occurring in TGDC is around 1 % [13,[28][29][30], though higher rates have been reported by tertiary or academic referral centers, ranging from 4.9 to 7.4 % [20,31,32]. In the present community practice based series, 3.2 % of TGDC contained an associated carcinoma.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The reported incidence of carcinoma occurring in TGDC is around 1 % [13,[28][29][30], though higher rates have been reported by tertiary or academic referral centers, ranging from 4.9 to 7.4 % [20,31,32]. In the present community practice based series, 3.2 % of TGDC contained an associated carcinoma.…”
Section: Discussionmentioning
confidence: 51%
“…Involvement of skeletal muscle may be seen, and should perhaps suggest upstaging to a pT3 tumor. Histologic examination of the thyroid in patients with thyroglossal duct cyst carcinoma may show a microscopic papillary carcinoma in approximately one-third of cases [29][30][31][32][33]. Among patients with thyroglossal duct cyst carcinoma who had a thyroidectomy in the present study, 32 % showed a synchronous papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 61%
“…It is thought that the prognosis is good and similar to that of papillary carcinoma of thyroid gland having cure rates in excess of 95%. Hence most authors consider a Sistrunk's operation to be adequate [9][10][11]. Others consider the possibility of multifocal origin and possible lymphatic spread to the thyroid, based on embryology.…”
Section: Discussionmentioning
confidence: 99%
“…They [14] also mentioned that addition of total thyroidectomy to Sistrunk procedure did not have signifi cant impact on survival especially young population below age 45 who constitutes low risk group. Plaza et al [15] recommended an algorithm for TGDC carcinoma to be treated with Sistrunk procedure without total thyroidectomy in low risk patients. They stratifi ed low risk patients as younger than 45 years, tumor less than 1.5 cm that is confi ned to the cyst, without distant metastasis and with normal thyroid gland on ultrasonography and no suspicious lymph nodes [15].…”
Section: Management Of Tgdc Carcinoma Varies and Includedmentioning
confidence: 99%
“…Plaza et al [15] recommended an algorithm for TGDC carcinoma to be treated with Sistrunk procedure without total thyroidectomy in low risk patients. They stratifi ed low risk patients as younger than 45 years, tumor less than 1.5 cm that is confi ned to the cyst, without distant metastasis and with normal thyroid gland on ultrasonography and no suspicious lymph nodes [15]. Because of the rarity of this disease, and lack of specifi c guidelines, some authors agreed with following the current guidelines for management of papillary thyroid carcinoma concluding that Sistrunk procedure is suffi cient for tumor less than 1 cm [13,16].…”
Section: Management Of Tgdc Carcinoma Varies and Includedmentioning
confidence: 99%